Lord of the wings [large type] - Andrews, Donna (Andrews, Donna. Meg Langslow mysteries., 2015)
"Reluctantly volunteering her home after a haunted house exhibit burns down during her town's over-the-top Halloween festival activities, Meg Langslow is challenged to save the day upon discovering a real murder victim among the creepy displays"--